Penerapan Metode Mind Mapping Berbantuan Media Torso untuk Meningkatkan Hasil Belajar Siswa Kelas XI pada Materi Sistem Gerak - Grasela Adythia Nawar; Yohana Makaborang; Anita Tamu Ina (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
This study aims to improve the learning outcomes of class XI MIPA 1 SMA Negeri 1 Waingapu students through the mind mapping method. This type of research is classified as Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of stages of planning, execution, action, evaluation, and reflection. The subjects of this study were class XI MIPA 4 students of SMA Negeri 1 Waingapu for the 2021/2022 school year, totaling 37 students, consisting of 15 male students and 22 female students. The data obtained in this study is in the form of student learning outcomes taken from the application of the mind mapping learning method. The instruments used are interview sheets, tests, and documentation. The results of research and data analysis in cycle I and cycle II are known that there is an increase in learning outcomes of class XI MIPA 4 SMA Negeri 1 Waingapu students for the 2021/2022 school year. This is shown by an increase in the percentage of student learning outcomes towards Biology lessons in the Motion System material from the results of mind mapping assignments in cycle 1, showing a percentage of student creativity of 54.14% with less creative categories and to 86.49% with very creative categories in cycle 2. Student learning outcomes also increased from a completion percentage of 46.64% in cycle I to 86.48% in cycle II.